دراسة إمكانية تأقلم بعض أصناف الزيتون المحلية والمستوردة في ظروف الزراعة في الساحل السوري - دواي فيصل; مخول جرجس (Latakia University Journal -Biological Sciences Series, 2019)
تم التوصل من خلال البحث إلى النتائج التالية: تفوق الصنفان "بيشولين" و" فرونتويو" معنوياً على بقية الأصناف المدروسة من حيث عدد العناقيد الزهرية في الفرع وعدد الأزهار في الفرع وكانت أقل قيمة لهاتين الصفتين في الصنف " درملالي " وبلغت 3.95 عنقود / فرع و44.52 زهرة / فرع كمتوسط لسنوات الدراسة. كانت أعلى قيمة لعدد الأزهار / عنقود الزهري في الصنف " جلط" (16.47 زهرة) وأقلها في الصنف " درملالي" (10.97 زهرة) ، وقد تفوقت الأصناف "جلط ، تانش، بيشولين ، فرونتويو" على كل من الأصناف "درملالي ، دعيبلي ، صوراني " (قيمة Lsd5% = 4.15) بينما لم يكن هناك فروق معنوية بين بقية الأصناف. كانت أعلى نسبة للأزهار الخنثى في الصنف "جلط" (95.63%) تلاه الصنفان " درملالي وفرونتويو" (93.66% و92.93 %) على التوالي ، وأقلها في الصنف "بيشولين" (59.49%). فيما يتعلق بنسبة العقد فكانت أعلى نسبة في الصنف "درملالي" (8.67%) كمتوسط للسنوات الثلاث، وأقل نسبة في الصنف "صوراني أبو شوكة" (1.74%). وقد تفوق الصنف درملالي على كافة الأصناف المدروسة (Lsd5%= 3.27). احتل الصنف " تانش " المرتبة الأولى من حيث متوسط وزن الثمرة في مرحلة نضج القطاف (4.92 غ)، بينما كان متوسط وزن الثمرة أقله في الصنف "فرونتويو" (1.51 غ) وقد تفوق الصنف تانش على بقية الأصناف في هذه الصفة (Lsd5% 0.67 ). وكانت أكبر قيمة لمتوسط نسبة النواة/ ثمرة في الصنفين "دعيبلي وفرونتويو" (25.45 % و25.43%) وأقل قيمة كانت في الأصناف " قيسي، جلط وبيشولين" (14.94 % و14.93% و15.65%) على التوالي. علماً بأن هذه الصفة تعد سلبية كلما كانت كبيرة والعكس صحيح. لم يكن هناك فروق معنوية بين الصنفين " درملالي ودعيبلي" من حيث عدد الأزهار في العنقود الزهري (10.97،11.36)؛ نسبة الأزهار الخنثى (93.66 ، 93.07)؛ متوسط نسبة الزيت (20.28 ، 19.89)، وهذا يستوجب القيام باختبارات وراثية للتأكد من أنهما ينتميان لصنف واحد أم لصنفين مختلفين. مما تقدم يمكن القول بأن الأصناف "بيشولين فرنسي، جلط، قيسي، صوراني، فرونتويو، تانش" لاتلائم ظروف البيئة الساحلية التي تزرع فيها أصناف الزيتون كمصدر للزيت بالدرجة الأولى ومن أجل التخليل بالدرجة الثانية. This study was conducted during the years 2000, 2001 and 2002, the following results have been obtained: Picholine and Frantoio varieties were significantly better than the other studied varieties in terms of the number of flower clusters and the number of flowers in the branch. The lowest numbers for these characteristics were in the Dremlali variety (3.95 clusters/branch and 44.52 flowers/branch) as a main calculation during the period of study. The highest number of flowers per flower cluster was in Gelet variety (16.47 flowers), and the lowest number was in the Dremlali variety (10.97 flowers). Gelet, Tanche, Picholine and Frantoio varieties were better than Daiably ,Dremlali and Sorany Abo Shoky (Lsd5%= 4.15). There were no significant differences among the other studied varieties. The highest percentage of hermaphrodite flowers was in varieties Gelet (95.63%), Dremlali (93.66%) and Frantoio (92.93%), and the lowest percentage was in Picholine variety (59.49%). The highest percentage of fruitage was in the Dremlali variety (8.67% as a main calculation during the period of study), and the lowest percentage was in Sorany Abo Shoky variety (1.74%). Dremlali variety was better than all other studied varieties (Lsd5%= 3.27). Tanche variety has ranked first in terms of the average of fruit weight in maturation and harvest period (4.92 g/fruit), and the lowest fruit weight was in Frantoio variety (1.51 g/fruit). Tanche variety was better in this character than all other studied varieties (Lsd5%= 0.67). The highest main value of the percentage of stone/fruit were for Daiably (25.45%) and Frantoio (25.43%) varieties, and the lowest main values was for Kaissy (14.99%), Gelet (14.93%) and Picholine (15.65%) varieties. High value of this aspect is considered to be negative. There were no significant differences between Dremlali and Daiably varieties in terms of the number of flowers in the flower cluster (11.36, 10.97); the percentage of hermaphrodite flowers (93.66, 93.07); the percentage of oil (20.28, 19.89); the main of fruit weight (3.92, 2.98). A genetic test must be conducted to prove if they are related to one variety or they are considered two different varieties.